Persepsi Mahasiswa Program Studi Ilmu Informasi Perpustakaan dan Kearsipan (IIPK) Mengenai Jasa Layanan Informasi di UPT Perpustakaan Universitas Negeri Padang - Indri Viollita; Bakhtaruddin Nst. (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper aims to determine: (1) student responses on Information Science Program for Libraries and Archives in the Information Services Unit, State University of Padang, and (2) the constraints faced by libraries in providing services to pemustakanya. To obtain information on the issue, conducted direct observation by means of questionnaires / questionnaires to students of Library and Information Sciences archives. Analyzing data descriptively. Penganalisian based on the data, it was concluded the following matters, namely there are several factors that affect services in libraries, among others: (1) The role and function of libraries (2) library collection (3) Facilities and Libraries (4) librarian. Based on the results of the questionnaire / poll that has been processed, it appears that the Administration Services Unit at the State University of Padang already said good although there are still shortcomings in terms of ministry. Keywords: information; observation; services; facilities